Emerging Ceramic-based Materials for Dentistry. (December 2014) - Denry, I.; Kelly, J.R.
Our goal is to give an overview of a selection of emerging ceramics and issues for dental or biomedical applications, with emphasis on specific challenges associated with full-contour zirconia ceramics, and a brief synopsis on new machinable glass-ceramics and ceramic-based interpenetrating phase composites. Selected fabrication techniques relevant to dental or biomedical applications such as microwave sintering, spark plasma sintering, and additive manufacturing are also reviewed. Where appropriate, the authors have added their opinions and guidance.